2014
DOI: 10.3989/ic.13.095
|View full text |Cite
|
Sign up to set email alerts
|

Modelización de tableros de obras de paso de luces cortas ejecutados con placa alveolar pretensada

Abstract: RESUMENLos métodos tradicionales de emparrillado plano utilizados para el cálculo de tableros conformados con placa alveolar pretensada no aportan suficiente precisión para determinar la influencia de fenómenos tales como la torsión sobre las placas o el rasante entre la capa de reparto y la propia placa. Se propone un nuevo método de modelización híbrido que permite cuantificar de forma más realista el mecanismo resistente de este tipo de tableros. La aplicación del método sobre un tablero tipo ha permitido o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Xiang et al [28] established a calculation model with a spring-hinged link system and found that the maximum errors of joint shear force, hinge joint transverse force, and hollow slab relative displacement were 0.475 kN/m, 3.832 kN/m and 0.00067 mm, respectively, which verified the accuracy and practicality of the method. Moreno-Padilla et al [29] proposed a new model that showed a good correlation between the numerical predictions and the behavior observed in reality. Dan et al [30] established a multibeam model connected by distributed springs to analyze the modal characteristics of a fabricated girder bridge.…”
Section: Introductionmentioning
confidence: 93%
“…Xiang et al [28] established a calculation model with a spring-hinged link system and found that the maximum errors of joint shear force, hinge joint transverse force, and hollow slab relative displacement were 0.475 kN/m, 3.832 kN/m and 0.00067 mm, respectively, which verified the accuracy and practicality of the method. Moreno-Padilla et al [29] proposed a new model that showed a good correlation between the numerical predictions and the behavior observed in reality. Dan et al [30] established a multibeam model connected by distributed springs to analyze the modal characteristics of a fabricated girder bridge.…”
Section: Introductionmentioning
confidence: 93%